Model Ekosistem Digital Terintegrasi Melalui Web Commerce Dan Media Sosial Dalam Meningkatkan Kinerja Penjualan Jasa Percetakan - Anggriani Syahputri; Bayu Winata; Dhea Ayu Syafitri; Ferdian Ansori; Lyra Aulia Syahbrina; Nanda Rifaldi Lubis; Nurhafis Oktaviani; Sania Shanti Dewi; Sarmila Sarmila; Suci Rahmadani Sitorus; Try Santi Kisria Darsih (Journal of Innovative and Creativity, 2026)
The development of digital technology encourages printing service businesses to adapt by utilizing an integrated digital ecosystem. This study aims to analyze the implementation of a digital ecosystem model based on web commerce and social media in improving the sales performance of printing services. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and literature studies. The results indicate that the integration of web commerce and social media can increase market reach, service efficiency, and sales volume of printing services. This study concludes that an integrated digital ecosystem model can be an effective strategy to enhance the competitiveness of printing service businesses in the digital era.